2007
DOI: 10.1002/art.22480
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining participation in prevention trials among systemic lupus erythematosus patients: a qualitative study

Abstract: Objective. A feasibility study for a trial of strategies for the prevention of atherosclerosis in patients with systemic lupus erythematosus (SLE) was stopped because of inadequate recruitment. There is little understanding of the factors influencing patients' decisions about participation in prevention trials. Our goal was to determine factors that patients with SLE consider in deciding about participating in prevention trials, to uncover concerns about SLE trials, and to investigate how study design and purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 18 publications
1
53
0
3
Order By: Relevance
“…While clinical trials, including vaccine trials, have been conducted in Puerto Rico with children, only one was double blinded and placebo controlled. [18][19][20][21][22][23][24] The difficulty in recruiting and retaining participants in clinical trials is well documented, [25][26][27][28] particularly among children. This has resulted in cost increases, implementation delays, failure to complete trials, and biased results.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While clinical trials, including vaccine trials, have been conducted in Puerto Rico with children, only one was double blinded and placebo controlled. [18][19][20][21][22][23][24] The difficulty in recruiting and retaining participants in clinical trials is well documented, [25][26][27][28] particularly among children. This has resulted in cost increases, implementation delays, failure to complete trials, and biased results.…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in cost increases, implementation delays, failure to complete trials, and biased results. [25][26][27][28] Contributing factors to recruitment and retention include lack of trust, inadequate knowledge, fear of side effects and risks, and clinical trial procedures. 25,26,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Although studies have been conducted to understand cultural barriers to participation and retention in clinical trials, none have been conducted in Puerto Rico.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altruistic motives are also known motivators to enter a clinical study (18)(19)(20), although a study from Romania revealed payment and free complete blood tests as motivators to participate (15). We aimed to increase the sense of contribution to science by presenting the study results through newsletters, booklets, and meetings for trial participants.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Arthritis Care & Research, Costenbader and colleagues present a number of interesting findings regarding individuals' decisions whether to participate in clinical prevention trials (1). The rationale for the study arose when recruitment for a randomized controlled trial aimed at prevention strategies for atherosclerosis in systemic lupus erythematosus (SLE) proved to be so difficult the trial was suspended.…”
mentioning
confidence: 99%